2015
DOI: 10.1007/s12663-015-0839-5
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Observation During Neck Dissection

Abstract: External jugular vein (EJV) is a major superficial vein in the neck which drains deeper parts of face and posterior scalp region. Although it follows a predicted pattern in formation, course and termination in general unusually it also exhibits variations which are clinically important. Gross variations in the incidence of these variations in EJV are noted. We report an anomalous course of EJV which drains into internal jugular vein in our case report. Knowledge about EJV and its origin, course and termination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The importance of sound anatomical knowledge is greatly emphasized throughout the literature and is necessary to ensure that clinical procedures are successfully performed in a safe manner (Van Schoor et al 2005;Prigge et al 2013). Anehosur et al (2015) suggested that knowledge of variations in venous patterns in the face and neck is of paramount importance for head and neck surgeons to avoid unnecessary hemorrhaging during surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of sound anatomical knowledge is greatly emphasized throughout the literature and is necessary to ensure that clinical procedures are successfully performed in a safe manner (Van Schoor et al 2005;Prigge et al 2013). Anehosur et al (2015) suggested that knowledge of variations in venous patterns in the face and neck is of paramount importance for head and neck surgeons to avoid unnecessary hemorrhaging during surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rao et al (2018), the complex embryological development of the vascular system can result in clinically relevant anomalies. These abnormalities can be unilateral or bilateral and are more often observed in the venous structures than the arterial distribution (Anehosur et al 2015). Different theories with regard to these anomalies have been postulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case showed a posterior tributary that joined with the IJV from the medial aspect of the sternocleidomastoid (SCM) and in another case, the tributary arose from under the SCM and drained into the lower third of the IJV [83]. In another case, the EJV was found to drain into the IJV instead of the subclavian vein, hence grouped as a posterior tributary [8]. In two instances, posterior tributaries of IJV were found during surgical dissection, one of which coursed deep to the posterior belly of the digastric, and another that coursed above the inferior belly of omohyoid [37].…”
Section: Tributariesmentioning
confidence: 99%